2020
DOI: 10.1002/cam4.3692
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anticancer treatment on cancer patients with COVID‐19: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 60 publications
3
49
1
1
Order By: Relevance
“…Our results indicated a high degree of similarity among the two treatment groups, with no significant difference appreciated between these groups with respect to ED utilization, ED imaging, indications and duration of hospitalization, and mortality. These results are supported by a recent study published by Liu et al, in which antineoplastic therapy did not result in any difference in disease severity or mortality [ 15 ]. Additionally, despite the concern about treatment-related complications, our study did not reveal any imaging findings or hospitalizations attributed primarily to cancer treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Our results indicated a high degree of similarity among the two treatment groups, with no significant difference appreciated between these groups with respect to ED utilization, ED imaging, indications and duration of hospitalization, and mortality. These results are supported by a recent study published by Liu et al, in which antineoplastic therapy did not result in any difference in disease severity or mortality [ 15 ]. Additionally, despite the concern about treatment-related complications, our study did not reveal any imaging findings or hospitalizations attributed primarily to cancer treatment.…”
Section: Discussionsupporting
confidence: 85%
“…As a result, they concluded that cancer surgery can be performed without higher risks of either severe events or death in patients with cancer along with COVID-19. We are pleased to see such work, as this is an important topic, with similar results published in other recent meta-analyses [ 2 , 3 ]. Because SARS-CoV-2 infections have been shown to worsen outcomes in patients with cancer compared with non-cancer patients, additional data are needed to examine the effect of cancer treatments on infection.…”
supporting
confidence: 74%
“…A cohort study on COVID-19 in breast cancer patients showed that hypertension and age (> 70 years) were associated with a higher risk of intensive care unit admission, death, or both [ 16 ]. With respect to tumor type, chemotherapy for patients with hematological malignancies has been reported to lead to higher mortality in COVID-19 [ 4 ]. Furthermore, there has been a case report describing severe COVID-19 virus reactivation following the resumption of chemotherapy for B cell acute lymphoblastic leukemia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some reports suggest that cancer patients could be at an increased risk of developing COVID-19-related complications, and many oncological societies have issued guidelines to assist clinical decisions and management during this crisis [ 1 , 2 ]. Many studies have verified the effect of recent anti-cancer treatment in patients with COVID-19; however, the results remain controversial [ 3 , 4 ]. Moreover, no study has evaluated the risk for post-COVID-19 patients who resumed their anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%